Immunosuppressive adherence after kidney transplantation in adult patients treated at an outpatient clinic: a better practice implementation project. Issue 3 (5th September 2021) - Campos, Caroline S.; Ferreira, Gustavo F.; Bastos, Kamille V.; da Costa Carbogim, Fábio; de Brito Poveda, Vanessa; de Araújo Püschel, Vilanice A.; dos Santos, Kelli B.
ABSTRACT: Objective: To evaluate the compliance of the practice with the evidence-based criteria in relation to interventions developed to improve the immunosuppressive adherence of adults in postkidney transplantation. Method: A best practice implementation project, based on the Joanna Briggs Institute's Practical Application of Clinical Evidence System and Getting Research into Practice audit tool for promoting change in health practice, was conducted. A baseline and a follow-up audit were conducted in a kidney transplant clinic, including a sample of kidney transplant patients with a maximum of 30 days postoperatively, and health professionals working in the post-transplant period. Results: The basic audit revealed that the parameters related to the professionals' knowledge did not reach adequate compliance; the involvement of patients in strategies to overcome barriers that interfere with nonadherence; guidelines for specific therapeutic regimens for patients and the prescription of immunosuppressants according to the patient's routine. To solve the identified weaknesses, training strategies were implemented with the professionals, follow-up by telephone contact with the patients and the elaboration and distribution of an educational booklet with guidance on the use of immunosuppressants, leading to an increase from 50 to 87.5% of conformity in the evaluated service. Conclusion: The evidence implementation project provided improvements in clinical practice behaviors. It demonstrated that there are strategies that facilitate the implementation of evidence regarding the promotion of interventions to improve immunosuppressive adherence. Additional audits are still needed to improve and assess the quality of interventions promoted by professionals regarding drug adherence in the post-transplant period, as well as to verify the behavior of patients, ensuring that the project will be maintained and supported.